Myoblast and ADSC coculture on conductive highly aligned nanofiber scaffolds for human skeletal muscle tissue engineering - Shi, Xiu; Cai, Aijia; Arkudas, Andreas; Horch, Raymund E.; Jabeen, Sehrish; Schubert, Dirk W.; Weisbach, Volker; Kratzer, Simon; Stumpfe, Maximilian; Mengen, Lilly (Biomedical Materials, 2025)
Conductive materials play a crucial role in enhancing functional performance in muscle tissue engineering. This study investigates the impact of the conductive polymer polyaniline (PANi) in Polycaprolactone (PCL)-collagen Type I (PCL-collagen I) nanofiber scaffolds designed to support the coculture of human adipose-derived stem cells (ADSCs) and myoblasts (Mbs). The effect of varying PANi concentrations (0%, 2%, 4%, 6%) in PCL-collagen I nanofiber scaffolds was evaluated concerning the cell alignment, differentiation and gene expression of cocultured Mbs and ADSC. Nanofiber scaffolds with different PANi concentrations were analyzed. Acetic acid was used as a non-toxic and biocompatible solvent for electrospinning the nanofibers.In vitroexperiments involved a 1:1 coculture of Mbs and ADSCs for up to 28 d on the scaffolds. The cell viability, differentiation and myotube morphology were assessed using live-dead-assay, CCK-8-assay, immunofluorescence staining and gene expression analysis. Scaffolds with 2% and 4% PANi showed a higher percentage of live cells compared to the control at both 7 and 28 d. The nanofibers with 2%, 4% and 6% PANi concentration showed promising results in terms of cell differentiation and myotube morphology. After 14 d, the scaffolds with 4% PANi showed superior cell differentiation with strong myotube alignment along the nanofibers. At higher PANi concentrations (6%), only the myotube width increased significantly, whereas 4% PANi resulted in a markedly higher myotube number. PCL-collagen I nanofibers incorporating PANi enhance myoblast alignment and differentiation compared to the control group, showing promise for muscle tissue engineering applications. The non-toxic solvent makes the nanofibers suitable for translational purposes. Furtherin vivostudies are needed to explore the full impact on cellular function and regeneration.
CRIS-Team Scopus Importer:2025-12-12
Keywords: conductive nanofiber; muscle tissue engineering; myogenic differentiation; polyaniline (PANi)

Vascularization of Poly-ε-Caprolactone-Collagen I-Nanofibers with or without Sacrificial Fibers in the Neurotized Arteriovenous Loop Model - Kratzer, Simon; Arkudas, Andreas; Himmler, Marcus; Schubert, Dirk W.; Schneidereit, Dominik; Bauer, Julian; Friedrich, Oliver; Horch, Raymund E.; Cai, Aijia (Cells, 2022)
Electrospun nanofibers represent an ideal matrix for the purpose of skeletal muscle tissue engineering due to their highly aligned structure in the nanoscale, mimicking the extracellular matrix of skeletal muscle. However, they often consist of high-density packed fibers, which might impair vascularization. The integration of polyethylene oxide (PEO) sacrificial fibers, which dissolve in water, enables the creation of less dense structures. This study examines potential benefits of poly-ε-caprolactone-collagen I-PEO-nanoscaffolds (PCP) in terms of neovascularization and distribution of newly formed vessels compared to poly-ε-caprolactone -collagen I-nanoscaffolds (PC) in a modified arteriovenous loop model in the rat. For this purpose, the superficial inferior epigastric artery and vein as well as a motor nerve branch were integrated into a multilayer three-dimensional nanofiber scaffold construct, which was enclosed by an isolation chamber. Numbers and spatial distribution of sprouting vessels as well as macrophages were analyzed via immunohistochemistry after two and four weeks of implantation. After four weeks, aligned PC showed a higher number of newly formed vessels, regardless of the compartments formed in PCP by the removal of sacrificial fibers. Both groups showed cell influx and no difference in macrophage invasion. In this study, a model of combined axial vascularization and neurotization of a PCL-collagen I-nanofiber construct could be established for the first time. These results provide a foundation for the in vivo implantation of cells, taking a major step towards the generation of functional skeletal muscle tissue.<br
Keywords: vascularization of nanofiber scaffolds; neurotization; neoangiogenesis; EPI loop model; AV loop model; PCL-collagen I-nanofiber scaffolds; polyethylene oxide